Long-term safety and tolerability of bapineuzumab in patients with Alzheimer's disease in two phase 3 extension studies. Issue 1 (December 2016) - Ivanoiu, Adrian; Pariente, Jérémie; Booth, Kevin; Lobello, Kasia; Luscan, Gerald; Hua, Lisa; Lucas, Prisca; Styren, Scot; Yang, Lingfeng; Li, David; Black, Ronald; Brashear, H.; et al.
Abstract Background Immunotherapy with monoclonal antibodies that target amyloid beta has been under investigation as a treatment for patients with Alzheimer's disease (AD). The 3000 and 3001 phase 3 clinical studies of intravenous bapineuzumab assessed safety and efficacy in patients with mild to moderate AD recruited in over 26 countries. This article describes the long-term safety and tolerability of bapineuzumab in the extension studies for these two protocols. Methods The long-term safety and tolerability of intravenous-administered bapineuzumab in patients with AD was evaluated in apolipoprotein E ε4 allele noncarriers (Study 3002, extension of Study 3000) and apolipoprotein E ε4 allele carriers (Study 3003, extension of Study 3001). Those receiving bapineuzumab in the parent study were continued at the same dose; if receiving placebo, patients began bapineuzumab. Bapineuzumab doses were 0.5 mg/kg in both studies and also 1.0 mg/kg in the noncarrier study. Clinical efficacy of bapineuzumab was also assessed in exploratory analyses. Results Because of lack of efficacy in two other phase 3 trials, the parent protocols were stopped early. As a result, Studies 3002 and 3003 were also terminated. In total, 492 and 202 patients were enrolled in Studies 3003 and 3002, respectively. In apolipoprotein E ε4 carriers (Study 3003), treatment-emergent adverse events occurred in 70.7 % of the patients who originally received placebo and 66.9 % of those who originally received bapineuzumab. In noncarriers, treatment-emergent adverse events occurred in 82.1 % and 67.6 % of patients who received placebo + bapineuzumab 0.5 mg/kg and placebo + bapineuzumab 1.0 mg/kg, respectively, and in 72.7 % and 64.3 % of those who received bapineuzumab + bapineuzumab 0.5 mg/kg and 1.0 mg/kg, respectively. Amyloid-related imaging abnormalities with edema or effusions were the main bapineuzumab-associated adverse events in both studies, occurring in approximately 11 % of placebo + bapineuzumab and 4 % of bapineuzumab + bapineuzumab groups overall. Exploratory analyses of clinical efficacy were not significantly different between groups in either study. Conclusions In these phase 3 extension studies, intravenous bapineuzumab administered for up to approximately 3 years showed no unexpected safety signals and a safety profile consistent with previous bapineuzumab trials. Trial registration Noncarriers (Study 3002): ClinicalTrials.govNCT00996918 . Registered 14 October 2009. Carriers (Study 3003): ClinicalTrials.govNCT00998764 . Registered 16 October 2009.